2009
DOI: 10.1118/1.3260839
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing non‐Pb radiation shielding materials using bilayers

Abstract: Depending on the x-ray quality, appropriate choices of two complementary metal-embedded elastomer layers can decrease the weight of radiation shielding garments by up to 25% compared to Pb-based elastomer garments while providing equivalent attenuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…MC calculations for the attenuating capabilities of a Ba + Bi bilayer combination were performed in an earlier study. 20 While no manufactured materials containing these metals were available for measurements at that time, the MC calculations showed that this bilayer combination should perform significantly better and more consistently than the other combinations modeled and measured. Since the earlier studies, several manufacturers have produced experimental material containing compounds incorporating these metals.…”
Section: Iiib Non-pb Compoundsmentioning
confidence: 94%
“…MC calculations for the attenuating capabilities of a Ba + Bi bilayer combination were performed in an earlier study. 20 While no manufactured materials containing these metals were available for measurements at that time, the MC calculations showed that this bilayer combination should perform significantly better and more consistently than the other combinations modeled and measured. Since the earlier studies, several manufacturers have produced experimental material containing compounds incorporating these metals.…”
Section: Iiib Non-pb Compoundsmentioning
confidence: 94%
“…[8][9][10][11][12][13][14][15] Most investigators have declined to measure the transmission of scattered radiation owing to concerns about x-ray tube loading and difficulties associated with measuring scattered radiation. One study did examine the performance of lead-composite aprons using scattered radiation from a 110 kVp fluoroscopy beam, 16 finding lead-composite garments to provide protection comparable to lead garments.…”
Section: Introductionmentioning
confidence: 99%
“…They can contain non-toxic fillers that provide effective radiation-shielding 102,103 . The plastics reinforced with carbon/graphite fiberare widely used as structural materials, due to their high hardness-weight ratio and superb mechanical and thermal properties.…”
Section: Resultsmentioning
confidence: 99%